Investigating Risk of Self-Harm by Young Aboriginal People with A History of Child Protection System Contact: Identifying Opportunities for Prevention - Leckning, Bernard; He, Vincent Yaofeng; Hirvonen, Tanja; Condon, John; Guthridge, Steven (International Journal of Population Data Science, 2020)
Introduction The Northern Territory (NT) population experiences amongst the highest rates of both child maltreatment and self-harm of any jurisdiction in Australia, especially amongst young Aboriginal people. This is a concern given the evidence linking child maltreatment to self-harm and suicide. However, few longitudinal studies have examined these associations by patterns of child protection system contacts that may represent opportunities for intervention, and none have identified the distinct pathways for Aboriginal children. Objectives and Approach This retrospective cohort study investigated the excess risk of self-harm hospital admissions (12-18 years) associated with different levels and timing of child protection contacts (aged <12 years) amongst Aboriginal children. The study used linked, de-identified, individual-level records from multiple agencies for 6,476 Aboriginal children born in the NT between 1999 and 2003. Results Over 70% (n=36/50) of the cohort who experienced self-harm had a history of child protection contact. The overall probability of self-harm increased as the level of contact with the child protection system increased. After adjusting for confounding, children with any level of child protection contact in middle childhood (5-11 years) only and across both early (0-4 years) and middle childhood were 3 to 9 times more likely to experience self-harm in adolescence compared to their peers in the general population. Conclusion / Implications The findings are consistent with evidence of intergenerational trauma impacting Aboriginal families and children and identifies middle childhood as a critical period in which the risk for self-harm emerges. There is a need for culturally appropriate family support and parenting programs to be available at all levels of the child protection system. Furthermore, hospitals should use a trauma-informed approach to assess and care for young Aboriginal people who present following self-harm. Reflections will be offered on the benefits of using data linkage for investigating rare outcomes in difficult-to-reach populations.